Three-dimensional and two-dimensional relationships of gangliogenesis with folliculogenesis in mature mouse ovary: a Golgi–Cox staining approach - Mohammad Ebrahim Asadi Zarch (Nature Portfolio, 2021)
Abstract The present study was set out to investigate two-dimensional (2D) and three-dimensional (3D) evaluations of ovarian nervous network development and the structural relationship between folliculogenesis and gangliogenesis in mouse ovaries. Adult mice ovarian tissue samples were collected from follicular and luteal phases after cardiac perfusion. Ovarian samples were stained by a Golgi–Cox protocol. Following staining, tissues were serially sectioned for imaging. Neural filaments and ganglia were present in the ovaries. In both 2D and 3D studies, an increase in the number and area of ganglia was seen during the follicular growth. The same pattern was also seen in corpora lutea development. However, in some cases such as ratio of ganglia number to follicle area, the ratio of ganglia area to follicular area, 2D findings were different compared with the 3D results. 3D analysis of ovarian gangliogenesis showed the possible direct effect of them on folliculogenesis. Golgi–Cox staining was used in this study for 3D evaluation in non-brain tissue. The results of 3D analysis of the present study showed that, in some cases, the information provided by 2D analysis does not match the reality of ovarian neuronal function. This confirmed the importance of 3D analysis for evaluation of ovarian function.